Associations between the implementation of telework strategies and job performance: Moderating influences of boundary management preferences and telework experience - Härtel, Tobias M.; Hüttemann, Dominik; Müller, Julia (Frontiers in Psychology, 2023)
Boosted by the COVID-19 pandemic, more than ever, an organization’s success depends on its teleworkers’ performance. However, little attention has been paid to the individual strategies implemented by teleworkers to achieve goals such as drawing boundaries between work- and private-life, working task-oriented and productively, and keeping social contact. We collected quantitative survey data of 548 teleworkers indicating their implementation of 85 telework strategies derived from scientific literature and popular media (e.g., working in a separate room, wearing work clothes at home), self-reported job performance, boundary management preferences, and telework experience. We identified (a) the implementation of telework strategies, (b) associations with job performance, (c) divergences between the implementation and the performance association, and (d) moderating influences of boundary management preferences and telework experience. The results suggest that the most implemented telework strategies tend to be the ones most positively associated with job performance. These telework strategies serve goals related to working task-oriented and productively by adopting a conducive work attitude as well as keeping social contact by using modern communication technology rather than goals related to drawing boundaries between work- and private-life. The findings underscore the benefits of expanding a narrow focus on telework strategies stemming from boundary theory to unravel telework strategies’ puzzling impacts on (tele-) work outcomes. Also, taking a person-environment fit perspective appeared to be a promising approach to tailor evidence-based best practice telework strategies to teleworkers’ individual preferences and needs (boundary management preferences and telework experience).